(untitled) (Boca Raton, FL, 2013)
Fluctuation theory is an important tool for the analysis and understanding of many aspects of chemistry, chemical engineering, and biophysics occurring in solutions. It is the most complete and accurate approach but is often underused and underappreciated. This book outlines the theory, provides a tutorial on how to calculate various properties from both experiment and simulation, and reviews applications covering a wide variety of areas of research. It summarizes the potential use of fluctuation theory in a variety of research
Keywords: Solution (Chemistry),Fluctuations (Physics),Giải pháp (Hóa học),Biến động (Vật Lý)